(untitled) (Bangladesh Journal of Botany, 2014)
The enzymatic activity of Thermomyces lanuginosus BPJ-10 and Rhizomucor pusillus BPJ-2 were observed through qualitative screening programme which was demonstrated by the hydrolysis of substrate on solid media. Both the fungi exhibited potential xylanolytic and pectinolytic activities whereas no cellulase activity was observed in T. lanuginosus BPJ-10 and very low cellulase activity was found in R. pusillus BPJ- 2. The optimum temperature for mycelial growth of T. lanuginosus BPJ-10 and R. pusillus BPJ-2 were found to be 50 and 45°C, respectively, whereas the optimum pH for both of them were 6.5 and 5, respectively. Out of five culture media used, both the fungi showed maximum radial mycelia growth on Potato Dextrose Agar. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18021 Bangladesh J. Bot. 42(2): 207-213, 2013 (December